2007
DOI: 10.1258/095646207779949899
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported 'safe sex' among female sex workers in Mombasa, Kenya—PSA analysis

Abstract: We assessed the validity of self-reported sex and condom use by comparing self-reports with prostate-specific antigen (PSA) detection in a prospective study of 210 female sex workers in Mombasa, Kenya. Participants were interviewed on recent sexual behaviours at baseline and 12-month follow-up visits. At both visits, a trained nurse instructed participants to self-swab to collect vaginal fluid specimens, which were tested for PSA using enzyme-linked immunosorbent assay (ELISA). Eleven percent of samples (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 27 publications
5
42
2
Order By: Relevance
“…A revised calculation of unmet need which includes inconsistent (no condom use at last sex) condom users resulted in a greater (almost quadrupled) level of unmet need in this population. This revised estimate may not be entirely exact and hence may neither precisely reflect actual behaviour nor correct for potential response biases (a difficulty inherent in sexual behaviour research [13][14][15] ). Yet, it does reflect the importance of considering the correct and consistent use of condoms when describing the contraceptive needs of this population.…”
Section: Discussionmentioning
confidence: 99%
“…A revised calculation of unmet need which includes inconsistent (no condom use at last sex) condom users resulted in a greater (almost quadrupled) level of unmet need in this population. This revised estimate may not be entirely exact and hence may neither precisely reflect actual behaviour nor correct for potential response biases (a difficulty inherent in sexual behaviour research [13][14][15] ). Yet, it does reflect the importance of considering the correct and consistent use of condoms when describing the contraceptive needs of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted studies [2][3][4]7,[12][13][14][15][16] have typically employed only a single PSA assay. Our findings indicated a remarkable consistency of biomarker results regarding the presence or absence of semen exposure across the three PSA assays.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have compared PSA measurement with self-reported condom use and use problems suggest that PSA provides a more complete measure of condom failure during vaginal intercourse [13][14][15][16]. Methods for measuring PSA, however, vary in characteristics, performance and cost, and their comparability with respect to assessing condom performance has not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…While the reasons for misreporting in surveys are well-known (e.g., social desirability bias, recall bias), efforts to identify who is more likely to have discrepancies between self-reported survey data and biomarkers, including PSA, have had little success [12,[19][20][21]. In this study, we found that for several women in Group C (concordant), partner influences played a dominant role in their account of why they had unprotected sex, unlike women in Groups A and B (discordant).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies also show that PSA degrades rapidly in the vagina, returning to baseline levels in 24-48 h after exposure [18]. Studies comparing PSA test results with self-reported sexual behaviors have identified high levels of discordance between the two, confirming concerns about the under-reporting of unprotected sexual activity and over-reporting of condom use [7,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%